2013
DOI: 10.1002/hep.26678
|View full text |Cite
|
Sign up to set email alerts
|

Steroid use in acute liver failure

Abstract: Background/Aims Drug-induced and indeterminate Acute Liver Failure (ALF) might be due to an autoimmune-like hepatitis that is responsive to corticosteroid therapy. The aim of this study was to evaluate whether corticosteroids improve survival in fulminant autoimmune hepatitis, drug-induced or indeterminate ALF, and whether this benefit varies according to the severity of illness. Methods We conducted a retrospective analysis of autoimmune, indeterminate and drug-induced ALF patients in the Acute Liver Failur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
132
1
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(140 citation statements)
references
References 22 publications
4
132
1
3
Order By: Relevance
“…55,56 A more recent study from the ALFSG corroborated this, showing no improvement in overall survival in drug-induced, indeterminate or autoimmune ALF (61% versus 66%, p=0.41). 57 In fact, lower survival was observed in those patients with the highest model for end stage liver disease scores (>40) after corticosteroid therapy (30% versus 57%, p=0.03). NAC has a well-established role in paracetamol-induced ALF 44 although it is now also recommended in selected cases of non-paracetamol ALF.…”
Section: Acute Liver Failurementioning
confidence: 90%
“…55,56 A more recent study from the ALFSG corroborated this, showing no improvement in overall survival in drug-induced, indeterminate or autoimmune ALF (61% versus 66%, p=0.41). 57 In fact, lower survival was observed in those patients with the highest model for end stage liver disease scores (>40) after corticosteroid therapy (30% versus 57%, p=0.03). NAC has a well-established role in paracetamol-induced ALF 44 although it is now also recommended in selected cases of non-paracetamol ALF.…”
Section: Acute Liver Failurementioning
confidence: 90%
“…use was also identified to be an independent predictor of an improved SS rate. These findings indicated that intervention with corticosteroids was effective in preventing the disease progression and improving the prognosis of ALF and SALF, which was inconsistent with the results reported by Karkhanis et al (20). The discrepancy in the results in these two studies may be due to the different criteria used to define SS.…”
Section: Discussionmentioning
confidence: 59%
“…The discrepancy in the results in these two studies may be due to the different criteria used to define SS. In the present study, SS was defined as survival without transplantation until 24 weeks, whereas the Karkhanis et al (20) study defined SS as survival without transplantation for only 21 days. It is important to note that many patients surviving to 3 weeks may succumb to liver failure after 4-24 weeks.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…However, this increases sepsis risk and may preclude definitive LT. One study suggested that in cases of ALF due to immune-mediated pathologies, corticosteroids did not improve survival. 12 The majority of these patients are…”
Section: Specific Therapiesmentioning
confidence: 99%